The Western and Chinese exercise training for blood pressure reduction among hypertensive patients: An overview of systematic reviews - Tsoi, Kelvin; Lam, Amy; Tran, Joshua; Hao, Ziyu; Yiu, Karen; Chia, Yook Chin *; Turana, Yuda; Siddique, Saulat; Zhang, Yuqing; Cheng, Hao Min; Wang, Ji-Guang; Kario, Kazuomi; et al. (Wiley Open Access, 2023)
Hypertension remains the world's leading cause of premature death. Interventions such as exercise, diet modification, and pharmacological therapy remain the mainstay of hypertension treatment. Numerous systematic reviews and meta-analyses demonstrated the effectiveness of western exercises, such as aerobic exercise and resistance exercise, in reducing blood pressure in hypertensive patients. There is recently emerging evidence of blood pressure reduction with Chinese exercises, such as Tai Chi, Baduanjin, and Qigong. The current overview of systematic reviews aims to evaluate the quality and descriptively summarize the evidence for the effectiveness of western and Chinese exercises for hypertension management. Thirty-nine systematic reviews were included in this overview, with 15 of those being on Chinese exercise. Evidence suggests that exercise training, regardless of Western or Chinese exercise, generally reduced both systolic and diastolic blood pressure. High-intensity intermittent training did not further reduce blood pressure when compared to moderate-intensity continuous training. Conflicting results on the effectiveness of blood pressure reduction when comparing Chinese and Western exercise training were observed. This suggests the comparable effectiveness of Chinese exercise training, in particularly Tai Chi, to general or aerobic exercise training in terms of blood pressure reduction. The Chinese exercise modality and intensity may be more suitable for the middle-aged and elderly population.